PRECEDE- PROCEED Model on Determinants of Completeness Immunization Status among Infants in Bangkalan District, Madura - Lidia Aditama Putri; Yulia Lanti Retno Dewi; Setyo Sri Rahardjo (Masters Program in Public Health, Sebelas Maret University, 2017)
Background: Universal Child Immunization is a government program aimed at preventing infectious diseases. However, its target level has not been attained. Bangkalan is one of the districts with low immunization coverage. This study aimed to analyze PRECEDE-PROCEED model on determinants of complete immunization status among infants in Bangkalan District, Madura.Subjects and Method: This was an analytic observational study with cross-sectional design. The study was conducted at 10 community health centers in Bangkalan, Madura, from August to October, 2017. A total sample of 200 infants aged 9-12 months were selected by cluster sampling with community health center serving has the cluster. The dependent variable was completeness of immunization status. The independent variable were education, knowledge, maternal job status, attitude, distance to health facility, information exposure, family support, and health personnel support. The data was collected using questionnaire and analyzed by path analysis.Results: Completeness of immunization status was increased by positive maternal attitude (b=0.82; 95% CI= 0.10 to 1.55; p= 0.027), strong health personnel support (b= 0.79; 95% CI = -0.10 to 1.67; p= 0.081), and information exposure (b= 1.52; 95% CI= 0.75 to 2.29; p= 0.001), but was decreased by distance to health facility (b= -1.28; 95% CI= -2.13 to -0.44; p= 0.003). Positive maternal attitude was increased by strong family support (b= 1.35; 95% CI= 0.71 to 2.00; p= 0.001) and better knowledge (b= 2.29; 95% CI= 1.06 to 3.54; p= 0.001). Better knowledge was increased by information exposure (b= 1.54; 95% CI= 0.58 to 2.51; p= 0.002). Strong family support was increased by maternal working outside the house (b= 0.64; 95% CI= 0.03 to 1.26; p= 0.040). Maternal working outside the house (b= 1.12; 95% CI= 0.51 to 1.75; p= 0.001) and better knowledge (b= 1.27; 95% CI= 0.42 to 2.13; p= 0.003) were increased by high level of education.Conclusion: Completeness of immunization status is increased by positive maternal attitude, strong health personnel support, and information exposure, but was decreased by distance to health facility.Keyword: determinant, universal child immunization, PRECEDE-PROCEED modelCorrespondence: Lidia Aditama Putri. Prodi Kebidanan di STIKES Insan Unggul Surabaya, Jln. Raya Kletek No. 4 Taman, Sidoarjo 61257, Jawa Timur. E-mail: liydya30@gmail.com. Mobile +6285230752110Journal of Health Promotion and Behavior (2017), 2(4): 291-301https://doi.org/10.26911/thejhpb.2016.02.04.01